The burning sea [videorecording (DVD)] - Rosenløw-Eeg, Harald; Gudmestad, Lars; Thorp, Kristine Kujath; Bjelland, Henrik; Larsen, Rolf Kristian; Christiansen, Anders Baasmo, 1976- (Magnolia Home Entertainment, 2022)
An oil platform dramatically goes down on the Norwegian coast, and researchers try to find out what happened when they realize this is just the start of something even more serious.